Publisher Correction: The gut–liver axis and the intersection with the microbiome. Issue 12 (December 2018) - Tripathi, Anupriya; Debelius, Justine; Brenner, David; Karin, Michael; Loomba, Rohit; Schnabl, Bernd; Knight, Rob
In the original version of Table 1 published online, upward arrows to indicate increased translocation of PAMPs were missing from the row entitled 'Translocation' for both the column on alcoholic liver disease and nonalcoholic fatty liver disease. This error has now been updated in the PDF and HTML version of the article.